Predator or prey? Effects of farm growth on neighbouring farms. (25th July 2022) - Appel, Franziska; Balmann, Alfons
Abstract: We provide explorative insights on how farms which manage strong and successful growth affect farms in their neighbourhoods through spatial competition for land. The study is based on an exploratory analysis of repeated framed experiments within the business game FarmAgriPoliS (Appel & Balmann, Ecological Complexity, 40, 2019). In particular, we analyse the spatial influences of different behavioural clusters of farm managers. Our analysis finds that farms which manage strong growth substantially affect the development of farms in a spatial neighbourhood of some 10 km. Although the influence on the neighbourhood decreases with distance, the functional correlations of farm growth as well as exits are neither linear nor exponential, but eventually rather wave‐like. We further discuss the spatial interdependence of farms and the related overlaps of the predator–prey phenomenon with the phenomena of farms' path dependency and agricultural structural change. We conclude that along with farmers' strategies and their abilities, the characteristics of their neighbours and the distances between neighbouring farms also determine who is 'predator' and who is 'prey'.